Nikkatsu Diamond Guys - Volume 2 - Saito, Buichi; Nakahira, Ko; Noguchi, Haruyaso (Arrow Video, 2016)
Nikkatsu, the oldest film studio in Japan, inaugurated a star system in the late 1950s, finding talent and contracting them to a series of wild genre pictures. This collection celebrates these Diamond Guys with three classic films from directors Buichi Saito (Lone Wolf and Cub: Baby Cart in Peril), Ko Nakahira (Crazed Fruit), and Haruyasu Noguchi, who is a new discovery for the West. [Cover]
Keywords: DVD-Video